2016
DOI: 10.15694/mep.2016.000144
|View full text |Cite
|
Sign up to set email alerts
|

That ‘mushy boxed fog feeling’: dental students’ evaluations of the social and behavioural sciences in dental education

Abstract: This article documents the experiences of two dental educators with responsibility for teaching the Social and Behavioural sciences components of an undergraduate dental programme in the United Kingdom (UK). Many dental undergraduates struggle to see the relevance of behavioural and social science components to their training as dentists, similar to the experiences of medical students. This opinion piece will outline some of the key challenges faced by dental students when studying a social and behavioural sci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Many dental undergraduates struggle to see the relevance of the behavioural and social sciences, preferring the technical aspects of dentistry over the social 53 and looking for a more practical application of the social and psychological theories they learn. 8,54 In this paper we assert that the ambivalence of dental students towards the BeSS may be attributed to two factors: the hegemony of the biomedical approach in dental education and the existence of a hidden curriculum. 55,56 First, the clinical focus of dentistry aligns itself with an epidemiological outlook on health, illness and disease.…”
Section: Knowledge Of Oral Healthcare Systemsmentioning
confidence: 94%
See 1 more Smart Citation
“…Many dental undergraduates struggle to see the relevance of the behavioural and social sciences, preferring the technical aspects of dentistry over the social 53 and looking for a more practical application of the social and psychological theories they learn. 8,54 In this paper we assert that the ambivalence of dental students towards the BeSS may be attributed to two factors: the hegemony of the biomedical approach in dental education and the existence of a hidden curriculum. 55,56 First, the clinical focus of dentistry aligns itself with an epidemiological outlook on health, illness and disease.…”
Section: Knowledge Of Oral Healthcare Systemsmentioning
confidence: 94%
“…64 Our practical experience of teaching BeSS to dental students has led us to recognise a hidden curriculum about BeSS where students struggle with the content of BeSS. 54 The mix of 'conceptual or empirical, quantitative or qualitative, and descriptive or analytical-or a combination of all these' 11 offered by BeSS can directly challenge the imminent, reductionist outlook of dental education. In addition, we also found that the attitude of some staff members towards the BeSS (especially those most likely to have been exposed to a traditional dental education) and the place of BeSS teaching in the curriculum can reinforce the perception that BeSS are not relevant to dental education.…”
Section: Knowledge Of Oral Healthcare Systemsmentioning
confidence: 99%
“…The importance of psychology for nursing education can be traced back to textbooks in the 1920s, but nursing educators still debate the best way to teach psychology to nursing students to highlight its relevance (de Vries & Timmins, 2012). Dental school faculty understand the role of psychology for dentistry, but students often fail to understand why they must take such courses (Neville & Waylen, 2016). Furthermore, many students may not be aware of how they can pursue their interests through psychology.…”
Section: Realizing Its Potentialmentioning
confidence: 99%